Space-time coding for broadband wireless communications (Wiley-Interscience, 2007)
This cutting-edge text presents the state of the art in space-time (ST) coded multi-antenna systems operating over broadband wireless mobile channels, including an analysis of the most recent research findings. Specifically, the authors focus on the algorithms and performance analysis of ST coded systems at the physical layer.